Clinical characteristics, serum albumin and eosinophil levels as risk factors for drug induced hepatitis in tuberculosis patients receiving fixed-dose combination anti-tuberculosis drug - Anastasia, Andriani Sheila; Somia, I Ketut Agus; Arisanti, Ni Luh Putu Eka; Candrawati, Ni Wayan; Kusumawardani, Ida Ayu Jasminarti Dwi; Artana, I Gusti Ngurah Bagus; Rai, Ida Bagus Ngurah (International Journal of Advances in Medicine, 2022)
Background: Drug-induced hepatitis (DIH) is a side effect of the usage of anti-tuberculosis (TB) drugs, which can cause alteration in treatment regiments and prolonged treatment. This study aim is to identify the risk factors that can be used to predict the occurrence of DIH on tuberculosis (TB) patients. Methods: This was a case-control study, conducted at Sanglah central general hospital in Denpasar from January to June 2021. Data collection was carried out through the medical records of inpatients and outpatients who received fixed-dose combination anti-TB drug. Results: There were 62 research samples which were divided into 31 samples in the case group and 31 samples in the control group. The clinical manifestations of DIH were vomiting (32.8%), nausea (15.7%), abdominal pain (13.1%), and hepatic encephalopathy (1.3%). Median time to onset of DIH was 18 (Interquartile range: 19) days. Low BMI was a significant risk factor for DIH (AOR=22.4; 95% CI 4.147-121.575; p<0.001). Other clinical characteristic variables such as age, female, extrapulmonary TB, positive HIV status, diabetes mellitus, hypoalbuminemia, and eosinophilia were not proven risk factors for DIH-TB. Conclusions: Low BMI was a significant risk factor for DIH. Other variables such as age, female, extrapulmonary TB, positive HIV status, diabetes mellitus, hypoalbuminemia, and eosinophilia were not risk factors for DIH in TB patients.